Status Anak Luar Nikah Dalam Hukum Waris (Studi Komperatif Antara Kitab Undang-Undang Hukum Perdata Dengan Kompilasi Hukum Islam) (Faculty of Sharia, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2011)
Based on the above explanation, the problem of inheritance law is about what and how the duty and rights about one’s wealth when he/she passed away to be given to the beneficiary. Thus, one aspect of inheretince the presence of the beneficiaries who have rights to earn certain wealth from the death. To decide who will earn the wealth from the death (the beneficiaries) usually decided by the rules of law of certain communities or the culturall-law applied by certain ethnic group.